Partisipasi Mahasiswa dalam Meningkatkan Kesadaran Masyarakat untuk Menjaga Kebersihan Lingkungan - Hendrianto Udjari; Mahesa Dzulsyafiqri Mu’id; Rommy Hardyansah; Pratolo Saktiawan; Sarwo Waskito (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental cleanliness is a crucial factor in creating a healthy and sustainable quality of life. However, low public awareness of maintaining cleanliness requires an empowerment approach based on local potential. This community service activity involved 82 students who actively participated in raising public awareness through the application of the Asset-Based Community Development (ABCD) method. This method emphasizes mapping and utilizing local potential as a basis for developing sustainable environmental behavior. Through the process of identifying assets, developing community skills, and collaborating with local institutions and associations, students were able to create educational and participatory interactions in efforts to maintain cleanliness. The results of the activity showed an increase in environmental cleanliness and a strengthening of community social capital, marked by increased collaboration between residents, students, and educational institutions. It was concluded that student empowerment through the ABCD approach was effective in raising public awareness of environmental cleanliness and has the potential to be developed sustainably with the support of educational institutions and local governments.